ENTERPRISE ARCHITECTURE APPROACHMENT FOR DESIGNING IT MASTER PLAN BASED ON ERP FOR WATER UTILITY COMPANY - Fatimah, Hilmi Azmi; Hermadi, Irman; Nurhadryani, Yani (Jurnal Aplikasi Manajemen, 2019)
A comprehensive planning document that is written in the IT Master Plan has the purpose of addressing the company's need and guiding the implementation process to minimize failure. But many IT master plan was not based on integrated and best practice adoption using ERP. The development of the IT master plan also does not use the proper enterprise architecture (EA) method. This research designed an IT master plan based on ERP using Enterprise Architecture approachment for water utility companies and adopt ERP best practice references model. The Enterprise Architecture's method was TOGAF ADM from a prelim phase, requirement management phase, vision architecture phase, business architecture phase, and information system architecture phase. This research gave the results of 23 system recommendations named IT Integrated Solution for water utility companies which consist of 10 integrated applications, 8 ERP modules, and 5 ERP Industry Solution-Utility (IS-U) modules. To get a comprehensive IT Master Plan based on ERP, the water company needs to pay attention to other stages of TOGAF ADM. There needs to be a study to be able to validate the IT Master Plan, which has been developed.